Posłannictwo uniwersytetów w świetle dokumentów kościelnych - Dyduch, Jan (Prawo Kanoniczne, 1995)
A Universities’ Mission in Light of the Church’s Documents A university has its source and origin in the Church, because the world’s first universities came into existence through the inspiration and initiative of the Church. In modern times, they are also being established by the Church and surrounded by Her care. The Church’s pastoral care refers not only to the Catholic universities but to all universities as well. The Church wants to be present there establishing dialogue between faith and learning and building a bond between culture and the Gospel. The Church is concerned that evangelization would take place within the universities and that they would become centers of evangelization. If the university’s community serves the truth and conveys to, and at the same time, serves man whom it should integrally form through education and formation, then it evangelizes. The Church’s presence in universities may be seen in various institutions, for example: Catholic universities, faculties of theology, departments of theological sciences, university parishes, students’ chaplaincy, committee of students’ pastoral care, etc.; however, the Church is present there, particularly, when the faithful - laity and clergy - give living witness to the Gospel through their words and lives.